Review of "Through the Reading Glasses" - Passila, Anne (Organizational Aesthetics, 2015)
Thank you ever so much for offering this opportunity to review the Through the Reading Glasses manuscript. It is a very important piece of art, as well as making an academic contribution. I have had a pleasure to become familiar with this text in various ways. One of the beauties of the Through the Reading Glasses manuscript is that it seems to be impossible – at least in the traditions of academic discourse – to define what it is about. To me each reading has provided new angles; I have found links to the lack of a feminist methodology in innovation studies; how to talk about social change and human diversity; arts as a specific form of knowledge and knowledge creation; discussions of creativity and imagination in a context of innovation studies and practice; awareness of power games and deep structural power relations we are constructing in organizational research and practice; a need for critical reflection on organizing; and unsettling conventional practices through the arts.